Patterns of Attachment in Early Infancy in Normative Samples, Alternative Caregiving Systems, and High Risk Infants [Patrones de Apego en la Infancia Temprana en Muestras Normativas, Contextos de Cuidado Alternativo, E Infancia de Alto Riesgo] - Guajardo-Sainz, H; Lecannelier-Acevedo, F (Sociedad Chilena de Pediatria, 2019)
Scientific evidence gathered over the last decades has demonstrated that early attachment is a vital process for the understanding, prevention, and intervention of people´s mental and physical health. However, information about the attachment system functioning in Chile is scarce. Objective: To describe attachment styles distribution in populations of children under different types of care. Subjects and Method: Through a retrospective descriptive method, 714 mother-child pairs (1 to 36 months-old) selected at random and purposefully, were assessed using the Strange Situation Procedure, Attachment during Stress Scale (ADS), and Student-Teacher Relationship Scale. The samples were collec-ted from randomly selected normative families, infants attending JUNJI nurseries and kindergartens, and infants from CONIN centers and who live in prison with their mothers. Results: The samples from six studies show the spectrum of the attachment system functioning in diverse conditions: 70% secure and 30% insecure, and 51.1% secure and 48.9% insecure in normative samples; 48.5% secure and 51.5% in secure in alternative care; 39.6% secure and 60.4% insecure, and 25% secure and 75% in secure styles in high-risk samples. Conclusion: the study presents interesting evidence on the attachment distributions in childhood, which allow reflecting on the uneven Chilean reality with regard to early social and emotional development. © 2019, Sociedad Chilena de Pediatria. All rights reserved.